2018
DOI: 10.3389/fpsyg.2018.01305
|View full text |Cite
|
Sign up to set email alerts
|

The Higher the Score, the Darker the Core: The Nonlinear Association Between Grandiose and Vulnerable Narcissism

Abstract: Narcissism is a truly Janusian phenomenon, consisting of both narcissistic grandiosity, exhibitionism, admiration-seeking, boldness, and dominance on the one hand, and narcissistic vulnerability, introversion, withdrawal, hypersensitivity, and anxiety on the other hand. While there is broad consensus that these two seemingly contradictory faces of narcissism can be empirically discerned and have different implications for psychological functioning and mental health, there is not yet agreement on whether grandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 66 publications
(134 reference statements)
7
62
0
1
Order By: Relevance
“…The strong association of pathological altruism to depression and social fears suggests there may be clinical implications of these constructs. Recent research has pointed out the clinical implications of narcissism, particularly vulnerable narcissism (Jauk and Kaufman, 2018;Kaufman et al, 2018). Since we found a strong correlation between pathological altruism and vulnerable narcissism, the same recommendations that apply for vulnerable narcissism may also apply here, such as helping those scoring high in pathological altruism have a more stable self-esteem, increase healthy assertiveness of one's own needs, and increase psychological flexibility (the opposite of experiential avoidance; see Hayes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong association of pathological altruism to depression and social fears suggests there may be clinical implications of these constructs. Recent research has pointed out the clinical implications of narcissism, particularly vulnerable narcissism (Jauk and Kaufman, 2018;Kaufman et al, 2018). Since we found a strong correlation between pathological altruism and vulnerable narcissism, the same recommendations that apply for vulnerable narcissism may also apply here, such as helping those scoring high in pathological altruism have a more stable self-esteem, increase healthy assertiveness of one's own needs, and increase psychological flexibility (the opposite of experiential avoidance; see Hayes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The mean age was 37.12 (SD = 11.30) years; 0.80% (seven participants) did not complete high school, 42.30% completed high school, 56.90% had a bachelor's degree or higher. The research reported here is part of a larger project on personality; part of the data were previously published and the study procedure was described in greater detail (Jauk and Kaufman, 2018). The study was carried out in accordance with the relevant guidelines and regulations.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…(17)]. Our recent studies suggest that both aspects might be intertwined at high grandiosity (18, 19). Concurrent grandiosity and vulnerability are referred to as pathological narcissism (20).…”
Section: Narcissismmentioning
confidence: 96%
“…At the same time, clinical psychology research (Pincus and Lukowitsky, 2010) has indicated that people with narcissistic personality disorder have co-occurring grandiose and vulnerable narcissism states. Further studies (Jauk and Kaufman, 2018) have confirmed their independence for the general population, whereas people high on grandiose narcissism might display both (grandiose and vulnerable) aspects. Common to high-intensity grandiose narcissism and vulnerable narcissism is antagonism (Jauk and Kaufman, 2018;Weiss et al, 2019).…”
Section: Narcissismmentioning
confidence: 83%
“…Further studies (Jauk and Kaufman, 2018) have confirmed their independence for the general population, whereas people high on grandiose narcissism might display both (grandiose and vulnerable) aspects. Common to high-intensity grandiose narcissism and vulnerable narcissism is antagonism (Jauk and Kaufman, 2018;Weiss et al, 2019). Back et al (2013) specified two strategies of grandiose narcissism: admiration and rivalry.…”
Section: Narcissismmentioning
confidence: 83%